Role of public spaces in old urban texture - Panahi, Siamand; Sahar , Farnia (2008)
In the world, every object requires preserver and reinforcement in order to survive. Every article which stops movement is condemned to die. So, one of the best and simple ways of survival is sustaining to movement. The best solution for survival of an object is the preservation of its movement. The main solution for survival of an urban texture is continuity of important urban public and comprehensive places. In this article, public spaces such as cultural, religious, governmental, and scientific centers are introduced as important urban centers and their roles in stability and survival of the city are expressed. For an instance, it will be referred to some religious and cultural spaces in Islamic countries. In simple words, the hypothesis of the research is defined as follows. Public spaces are hearts of cities. A way of their stability is the preservation of continuity and updating the survival of them.